2004
DOI: 10.3748/wjg.v10.i3.356
|View full text |Cite
|
Sign up to set email alerts
|

Activating mechanism of transcriptor NF-kappaB regulated by hepatitis B virus X protein in hepatocellular carcinoma

Abstract: AIM:To investigate the mechanism and significance of NF-κB activation regulated by hepatitis B virus X protein (HBx) in hepatitis B virus (HBV)-associated hepatocellular carcinoma (HCC). METHODS:The expression levels of HBx, p65, IκB-α and ubiquitin were detected by immunohistochemistry in HCC tissue microarrays (TMA) respectively, and IκB-α was detected by Western blot in HCC and corresponding liver tissues. RESULTS:The percentage of informative TMA samples was 98.8% in 186 cases with a total of 367 samples. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…Aberrant activation of NF-ĸB p65 was also present in HCC in this study as in a previous report [30]. We further observed a more frequent expression of NF-ĸB p65 in Etk/Bmx-positive HCC cases than in Etk/Bmx-negative cases, but the difference was not statistically significant.…”
Section: Discussionsupporting
confidence: 78%
“…Aberrant activation of NF-ĸB p65 was also present in HCC in this study as in a previous report [30]. We further observed a more frequent expression of NF-ĸB p65 in Etk/Bmx-positive HCC cases than in Etk/Bmx-negative cases, but the difference was not statistically significant.…”
Section: Discussionsupporting
confidence: 78%
“…Increasing evidence suggests that HBx-mediated nuclear factor κB (NF-κB) activation has been implicated in hepatic inflammation, regeneration, liver injury, and HCC. 6 In our previous report, the association between HBx-mediated NF-κB activation and TNF receptor 1 (TNFR1) has been suggested, 7 but our report lacked information regarding HBx involvement in the TNFR1 pathway, and how HBx stimulates NF-κB activity through TNFR1 has yet to be determined.…”
Section: Introductionmentioning
confidence: 86%
“…On the other hand, it has been demonstrated that HBx-activated NF-κB prevented mitochondria membrane depolarization and apoptosis, 17 but increasing evidences suggest that HBx-mediated NF-κB activation has also been implicated in hepatic inflammation, regeneration, liver injury, and HCC. 6 Furthermore, the impacts of HBx on hepatocyte apoptosis are also different, depending on additional orchestrated signals such as TNF-α or ethanol. 20 Our data have also shown that similar to the role of NF-κB activation in HBxinduced steatosis, NF-κB activation is also associated with fulminant hepatitis induced by HBx/ TNF-α and, especially, activated NF-κB is required for the induction of apoptosis through ROS production and loss of mitochondrial membrane potential induced by HBx/TNF-α (Fig.…”
Section: Tnfr1 Contributes To the Hbx Promotion Of Tnf-α-induced Apopmentioning
confidence: 99%
“…Some studies have shown that HBx can induce tumor proliferation and invasion through down-regulating the function of P53 [23,24] , up-regulating the expression of survivin [25] , activating with several important cell signaling pathways, including PKB/Akt [26] , RAS/RAF/MAPK [27] , wnt/β-catenin [28] and NF-κB [29] . It has also proved that www.wjgnet.com…”
Section: Discussionmentioning
confidence: 99%